Determinants of Corporate Investment in China : Evidence From Cross-Country Firm Level Data - Geng, Nan (IMF Working Papers; Working Paper, 2012)
This paper analyzes the evolution of investment in China, its main features, and its key determinants. In recent years, manufacturing, real estate, and infrastructure have been the main drivers of investment. Investment remains largely concentrated in coastal areas, but there has been a shift to greater investments inland in recent years. The empirical analysis of the determinants of investment indicates that financial variables, such as interest rates, the exchange rate, and the depth of the domestic capital market are important determinants of corporate investment. The results suggest in particular that financial sector reform, including that which deregulates and raises real interest rates as well as appreciates the real effective exchange rate, would lower investment and help rebalance growth away from exports and investment toward private consumption.